Clinical implications of real-time optic nerve sheath diameter assessment via critical care ultrasound in intracranial hypertension - Zhang, Nan; Liang, Meng; Shao, Tenghao; Li, Ning; Wang, Kuo; Sun, Shuo; Sun, Tao (Frontiers in Neurology, 2025)
ObjectivesThis study aims to assess the clinical value of dynamic monitoring of optic nerve sheath diameter using critical care ultrasound in the management of patients with intracranial hypertension.MethodsA total of 130 patients with craniocerebral injuries, treated at the Department of Critical Care Medicine of the Affiliated Hospital of Hebei University from January 2021 to November 2022, were selected and randomly assigned to either the control group (65 patients) or the observation group (65 patients). Patients in both groups were monitored based on clinical symptoms, cranial CT findings, and optic nerve sheath diameter (ONSD). The control group received standard osmotic therapy to manage intracranial pressure (ICP), while the observation group was guided accordingly. Comparative analyses were conducted on Acute Physiology and Chronic Health Evaluation II (APACHE II) scores, Glasgow Coma Scale (GCS) scores, duration of ICU stay, and mechanical ventilation time between the two groups.ResultsOn the 28th day, the APACHE II scores of patients with craniocerebral injuries in both groups were significantly lower compared to admission scores, while GCS scores were higher (P < 0.05). Compared to conventional management, the observation group showed a 15% reduction in APACHE II scores, a 20% decrease in ICU stay duration, and a 25% reduction in mechanical ventilation time by day 28 post-admission. The observation group also showed a higher proportion of patients with favorable prognoses and a significant reduction in severe disability and vegetative survival rates (P < 0.05).ConclusionDynamic monitoring of ONSD using bedside critical care ultrasound has proven effective in guiding osmotic therapy for patients with intracranial hypertension. This approach significantly reduces ICP, offers a reliable basis to opt for subsequent treatments, and effectively lowers the rate of disability while improving patient prognosis.